Effect of binder/plasticizer ratios in aqueous-based tape casting on mechanical properties of bovine hydroxyapatite tape - Chanyapat Khamkasem (2018)
This work studied the properties of bovine hydroxyapatite (BHA) tapes using the aqueous-based tape casting technique, as a function of binder/plasticizer ratios. BHA slurries with various amounts of poly(vinyl alcohol) (PVA) as binder and Glycerol as plasticizer were prepared and tape casting. Mechanical properties of green and sintered BHA tapes and their microstructure were investigated. The result showed that the tensile strength of green tapes increased with the binder/plasticizer ratio and the flexural strength of sintered tapes decreased with increasing binder/plasticizer ratio. © 2013 Copyright Taylor and Francis Group, LLC.